PRIMULINA VERSICOLOR AND P. ALUTACEA SPP. NOV. (GESNERIACEAE), TWO NEW SPECIES WITH YELLOW FLOWERS FROM NORTHERN GUANGDONG, CHINA - Pan, Bo; Wang, Bing-Mou; He, Jin-Yan; Wen, Fang (Edinburgh Journal of Botany, 2016)
Two new Primulina species with yellow flowers, Primulina versicolor F.Wen, B.Pan & B.M.Wang and P. alutacea F.Wen, B.Pan & B.M.Wang (Gesneriaceae), from Guangdong, China are described and illustrated.
Keywords: Gesneriaceae; Guangdong; new species; Primulina; taxonomy